Behind the deviation of Islamic banks from shariah principles - Moh. Baqir Ainun (STIE Perbanas Surabaya, 2020)
This study examines the causes of Islamic banks deviated from shariah principles. It also explores why the Islamic bank deviates from shariah principles. This study used a qualitative method with in-depth interviews with employees and customers of one of the Islamic banks in Sumenep Indonesia. This study was divided into two steps. First, examine whether Islamic bank deviates from shariah principles. Second, examine what causes Islamic banks to deviate from shariah principles. The results of this study found that the causes of Islamic banks deviated from shariah principles are the existence of competition between Islamic banks and the reality of profit targets that must be achieved. The findings of this study contribute to providing information to the public who criticize Islamic banks so that they understand the difficult conditions of Islamic bank to adhere perfectly to shariah principles so that the public do not always blame Islamic bank for deviations committed and do not condemn it.